2002
DOI: 10.1080/107175402753413172
|View full text |Cite
|
Sign up to set email alerts
|

Low Concentrations of Chlorpromazine and Related Phenothiazines Stimulate Gene Transfer in HeLa Cells Via Receptor-Mediated Endocytosis

Abstract: Chlorpromazine and related phenothiazine antipsychotic compounds at the low concentration of 10(-5) M stimulated luciferase pRSVL DNA uptake and expression in HeLa cells. On the other hand, chloroquine at a 10(-5) M was without effect at this low concentration. However, at the higher normally used concentration of 10(-4) M (100 microM), chloroquine strongly stimulated luciferase expression and activity. Unfortunately, at 10(-4) M, the phenothiazines were toxic to the cells and could not be tested at this conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Very low amounts of inhibitors showed non‐significant paradoxical effects with a trend for an enhanced uptake of peptide. This observation is in accordance with earlier reports, but so far lacks a definite explanation . After establishing the optimal doses of inhibitors, internalization experiments with DCs and the Melan‐A peptides or ovalbumin were performed.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Very low amounts of inhibitors showed non‐significant paradoxical effects with a trend for an enhanced uptake of peptide. This observation is in accordance with earlier reports, but so far lacks a definite explanation . After establishing the optimal doses of inhibitors, internalization experiments with DCs and the Melan‐A peptides or ovalbumin were performed.…”
Section: Resultssupporting
confidence: 91%
“…The Melan‐A‐TAT fusion peptide [CELAGIGILTVRKKRRQRRR, Melan‐A sequence underlined] was synthesized using standard fluorenylmethoxycarbonyl (Fmoc) chemistry. The N‐terminal Cys residue was added to enable coupling of Alexa Fluor 488 (Alexa488) C 5 maleimide (Invitrogen, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Wagner et al [7] suggested that the ability of chloroquine to increase the pH results in inhibition of DNA degradation and is responsible for the enhanced transfection efficiency in the presence of this drug. Hawtrey et al [29] proposed that the feature of removing H + -ions in endosomal compartments may not be the most important physiological action both of quinolines and phenathiazines, as the concentration of 10 µM of basic chlorpromazine present in the endosomes is too low to significantly affect the pH in these vesicles. Supporting the latter finding is the recent observation that endosomal escape of polymeric gene delivery complexes is not necessarily enhanced by polymers buffering at low pH [30].…”
Section: Discussionmentioning
confidence: 99%
“…Hawtrey's research group demonstrated the stimulation of a luciferase pRSVL DNA uptake and expression in HeLa cells at low concentrations (10 -5 M) of CPZ and related antipsychotic phenothiazine compounds [148]. Higher concentrations of phenothiazines were toxic to the cells, and could not be tested.…”
Section: Cytotoxicitymentioning
confidence: 99%